Cover Feature: Synthetic Phosphodiester‐Linked 4‐Amino‐4‐deoxy‐l‐arabinose Derivatives Demonstrate that ArnT is an Inverting Aminoarabinosyl Transferase (ChemBioChem 23/2019). (8th November 2019) - Olagnon, Charlotte; Monjaras Feria, Julia; Grünwald‐Gruber, Clemens; Blaukopf, Markus; Valvano, Miguel A.; Kosma, Paul
Abstract : The action of a membrane‐embedded lipid‐to‐lipid glycosyltransferase (ArnT) on a synthetic lipid‐shortened phosphodiester derivative of 4‐amino‐4‐deoxy‐L‐arabinose (Ara4N) forms a new phosphodiester linkage to the lipid A part of bacterial lipopolysaccharides. The substitution by Ara4N is a major mechanism contributing to the antimicrobial resistance of Gram‐negative bacteria. The Burkholderia cenocepacia enzyme shows exquisite specificity concerning the stereochemistry at the anomeric center and the double bond of the prenyl chain. Models have been generated with PyMOL (Schrödinger Software) from PDB entries 6DFE and 5EZM. More information can be found in the full paper by P. Kosma et al. on page 2936 in Issue 23, 2019 (DOI: 10.1002/cbic.201900349 ).